Development of thalamocortical connections between the mediodorsal thalamus and the prefrontal cortex and its implication in cognition - Ferguson, Brielle R.; Gao, Wen-Jun (Frontiers in Human Neuroscience, 2015)
The mediodorsal thalamus (MD) represents a fundamental subcortical relay to the prefrontal cortex (PFC), and is thought to be highly implicated in modulation of cognitive ability. Additionally, it undergoes highly conserved developmental stages, which, when dysregulated, can have detrimental consequences. Embryonically, MD experiences a tremendous surge in neurogenesis and differentiation, and disruption of this process may underlie the pathology in certain neurodevelopmental disorders. However, during the postnatal period, a vast amount of cell loss in the MD occurs. These together may represent an extended critical period for postnatal development, in which disturbances in the normal growth or reduction of the MD afferents to the PFC, can result in PFC-dependent cognitive, affective, or psychotic abnormalities. In this review, we explore the current knowledge supporting this hypothesis of a protracted critical period, and propose how developmental changes in the MD contribute to the successful prefrontal cortical development and function. Specifically, we elaborate on the unique properties of MD-PFC connections compared with other thalamocortical afferents in sensory cortices, examine how MD-PFC innervation modulates synaptic transmission in the local prefrontal circuitry, and speculate on what occurs during postnatal development, particularly within the early neonatal stage, as well as juvenile and adolescent periods. Finally, we discuss the questions that remain and propose future experiments in order to provide perspective and novel insights into the cause of neuropsychiatric disorders associated with MD-PFC development.